Determination of 5-Hydroxymethyl-2-furaldehyde of Crude and Processed Fructus Corni in Freely Moving Rats Using In Vivo Microdialysis Sampling and Liquid Chromatography: Determination of 5-hydroxymethyl-2-furaldehyde by HPLC - Gang Cao; Yun Zhang; Xiaodong Cong; Baochang Cai; Hao Cai; Jian Feng (Iranian Journal of Pharmaceutical Sciences, 2011)
The purpose of this study was to develop a sensitive and fast microdialysis coupled with high-performance liquid chromatographic (HPLC) method for determination of 5-hydroxymethyl-2-furaldehyde (5-HMF) in free-moving rats after i.g. administration of the aqueous extract of crud Fructus corni and its processed products of jiuzheng pin (JZP). The concentration of 5-HMF in free-moving rats after i.g. administration of the water extract of Fructus corni and JZP was analyzed by microdialysis coupled with HPLC. Results demonstrated that the concentration of 5-HMF in microdialysate was 1.4951μg/l, but higher in rat microdialysate after i.g. administration of the aqueous extract of JZP (5.2662 μg/l). In conclusion, this method is proved to be rapid，accurate and simple. Real-time in vivo monitoring the concentration of 5-HMF provides the theoretical basis for further explaining the processing mechanism of F. corni.